Barriers and facilitators to BRCA genetic counseling among at‐risk Latinas in New York City. Issue 7 (16th September 2012) - Sussner, Katarina M.; Jandorf, Lina; Thompson, Hayley S.; Valdimarsdottir, Heiddis B.
Abstract Background Despite underuse of genetic services for hereditary breast and/or ovarian cancer risk among Latinas (including counseling and testing for BRCA mutations), there is little known about the barriers and facilitators to BRCA genetic counseling among this group. It is imperative to first understand factors that may impede Latinas seeking BRCA genetic counseling, as it is considered a prerequisite to testing. Methods Quantitative telephone interviews (N = 120) were conducted with at‐risk Latinas in New York City to investigate interest, barriers, and beliefs about BRCA genetic counseling. Statistical analyses examined predictors of intention to undergo BRCA genetic counseling. Results Despite moderate levels of awareness, Latinas held largely positive beliefs, attitudes, and knowledge about BRCA genetic counseling. Perceived barriers included logistic concerns (e.g., where to go, cost/health insurance coverage), emotional concerns (e.g., fear, distress), and competing life concerns (e.g., too many other things to worry about, too busy taking care of children or family members). Multivariate results showed that the strongest predictor of intention to undergo BRCA genetic counseling was competing life concerns; Latinas with more competing life concerns were less likely to intend to undergo BRCA genetic counseling (p = 0.0002). Other significant predictors of intention included perceived risk of carrying a BRCA mutation (p = 0.01) and referral by their physician (p = 0.02). Conclusion Educational efforts to promote BRCA genetic counseling among at‐risk Latinas and increase referrals by their physicians should incorporate discussion of perceived barriers to counseling, such as competing life concerns that Latinas may need to overcome in order to seek genetic counseling. Copyright © 2012 John Wiley & Sons, Ltd.